Tentative interpretive standards for disk susceptibility tests with moxalactam (LY127935). - Barry, A L (1980)
Moxalactam (LY127935; 6059-S) is a new beta-lactam antibiotic. We propose tentative zone standards for agar diffusion susceptibility tests with 30-microgram disks. The final selection of minimal inhibitory concentration breakpoints for definition of resistant and susceptible categories must await clinical experience with this drug. Some of the clinical questions to be answered are defined. A moderately susceptible (intermediate) category is proposed for those strains with minimal inhibitory concentrations of 16 or 32 microgram/ml (zones 15 to 22 mm in diameter). Strains with minimal inhibitory concentrations of greater than or equal to 64 microgram/ml are considered resistant, and those with minimal inhibitory concentrations of less than or equal to 8 microgram/ml are considered susceptible. Tests with 30-microgram disks did not satisfactorily separate strains with minimal inhibitory concentrations of 8 microgram/ml from strains requiring < 2 microgram/ml for inhibition, because the regression line became parabolic at concentrations of 2 microgram/ml and below. However, the disk tests were satisfactory for categorizing isolates into the above-described susceptible, moderately susceptible (intermediate), and resistant categories.